Peran Subak Dalam Optimalisasi Pengembangan Agrowisata Subak Kualon di Desa Sidan Kecamatan Gianyar Kabupaten Gianyar - Kardana, Pande Putu Ivan Witdi; Lestari, Putu Fajar Kartika; Pratiwi, Luh Putu Kirana (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2023)
Agriculture has the potential to become a new source of growth considering the market is quite large, especially since each district or in Bali has the potential for agricultural commodities. Subak is one of the world's cultural heritages which is a place for farming communities to carry out agricultural activities. Subak can also help farmers in improving the welfare of their families. Agrotourism as part of a tourist attraction with the aim of expanding knowledge, experience, recreation and business relations in agriculture. The purpose of this study is as follows: to determine the role of subak in optimizing the development of agro-tourism in Subak Kualon, Sidan Village, Gianyar. To find out the potential of Subak Kualon in the development of Agro-tourism in Sidan Gianyar Village. This type of research is qualitative and quantitative. The location in this study was Subak Kualon, Sidan Village, Gianyar District, Gianyar Regency. The time of implementation was 3 months, from November 2022 - January 2023. The results showed that the role of subak had an average percentage of 73.70% and was categorized as good. This is because the highest percentage is in the agricultural technical aspects of 79.72% and is categorized as good, the second highest percentage is the socio-cultural aspect of 74.20 which is categorized as good, the third is the environmental aspect with a percentage of 72.34 which is categorized as good and the fourth is the aspect economy of 71.77% and in the good category. Subak potential has an average percentage of 73.37% and is categorized as good. This is because the highest percentage is in the concept of accessibility with a percentage of 83.04% and is categorized as very good, the second highest percentage is attraction with a percentage of 72.00% and is categorized as good, the third is amenity with a percentage of 71.94 and is categorized as good and the the fourth is anciliary with a percentage of 68.51% and is categorized as good.